Urea-containing slow-release coated fertilizer and preparation method thereof

Through the bioenzyme polyurethane coating technology, the use of castor oil-based polyester polyol and hydrophobically modified starch, the problems of poor degradability, uncontrollable release and insufficient weather resistance of urea-coated fertilizer are solved, and the efficient and environmentally friendly urea sustained release effect is achieved, which is suitable for modern agriculture.

CN120574099AInactive Publication Date: 2025-09-02SHANDONG QISHANG CENTURY BIOTECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510771289.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-10
Publication Date
2025-09-02
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing urea-coated fertilizers have problems such as poor degradability, uncontrollable release, low nitrogen content and insufficient weather resistance, which is difficult to meet the functional needs of modern agriculture for smart fertilizers.

Method used

The bioenzyme polyurethane envelope technology is adopted to form a coating layer through the precise ratio and reaction design of components such as castor oil, castor oil-based polyester polyol, hydrophobically modified starch and high-temperature resistant biological enzymes, which regulates the release period and degradability of urea, and improves mechanical strength and environmental friendliness.

Benefits of technology

It has achieved high nitrogen content, controlled release period, and environmentally friendly sustained release effects of urea. It is suitable for agricultural planting and landscaping, with a degradation rate of up to 90%, excellent rainwater erosion resistance, improved nitrogen utilization rate, and can be adjusted for 30-120 days.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of fertilizers, in particular to a urea-containing slow-release coated fertilizer and a preparation method thereof. The urea-containing slow-release coated fertilizer comprises urea particles and a bio-enzyme polyurethane coating layer coated on the surfaces of the urea particles, and the bio-enzyme polyurethane coating layer comprises the following components in parts by mass: 10-20 parts of urea particles, 10-20 parts of urea particles and 10-20 parts of urea particles. Comprising the following raw materials: 20 to 25 parts of castor oil, 18 to 25 parts of castor oil-based polyester polyol, 25 to 30 parts of hydrophobic modified starch, 16 to 22 parts of diphenylmethane diisocyanate, 0.03 to 0.05 part of a catalyst, 1.5 to 2 parts of a dispersant, 1.5 to 2 parts of a high-temperature-resistant bio-enzyme, 2 to 3 parts of glycerin and 14 to 18 parts of N, N-dimethylformamide. The polyurethane coating layer material of the bio-enzyme is prepared through the cross-linked network design of the molecular level and the collaborative regulation and control of the macroscopic coating layer thickness, the balance among efficient nitrogen utilization, environmental friendliness, mechanical properties and weather resistance is achieved, and a solution with technical innovation and practical value is provided for the field of slow-release fertilizers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of fertilizers, and in particular to a urea-containing slow-release coated fertilizer and a preparation method thereof. Background Art

[0002] According to the Food and Agriculture Organization of the United Nations (FAO), the global population is projected to exceed 9 billion by 2050, necessitating an approximately 60% increase in agricultural production to feed this growing population. Crop production relies on the use of fertilizers. Urea is a typical fertilizer, and the one with the highest nitrogen content, commonly used in the cultivation of crops such as rice, wheat, and corn. However, urea dissolves rapidly upon contact with water, washing away some of its nutrients before they can be absorbed by crop roots, resulting in significant urea loss.

[0003] Traditional coated fertilizers often use materials such as sulfur and resin as a coating layer, which presents the following issues: 1) Poor degradability: Traditional materials are difficult to degrade in soil, easily causing environmental pollution. 2) Uncontrollable release: The rate of nutrient release is significantly affected by environmental factors, making it difficult to precisely match crop needs. 3) Low nitrogen content: The urea core is easily diluted by the coating material, resulting in a decrease in the effective nitrogen content. 4) Insufficient weather resistance: The coating layer is easily washed away by rain or mechanical damage, resulting in nutrient loss.

[0004] There is no urea-coated fertilizer combined with bio-enzyme polyurethane coating technology in the existing technology. This technology needs to achieve high nitrogen content, controllable release period and environmentally friendly characteristics at the same time. Summary of the Invention

[0005] To address the shortcomings of the existing technology, this application provides a urea-containing slow-release coated fertilizer and its preparation method. The urea-containing slow-release coated fertilizer prepared in this application has a high nitrogen content, a controllable release period, is environmentally friendly, highly degradable, and has excellent weather resistance and rain erosion resistance, making it suitable for agricultural planting, landscaping and other fields. The bio-enzyme polyurethane coating has excellent weather resistance, mechanical properties, and degradability. The release period (30-120 days) is controlled by the thickness of the bio-enzyme polyurethane coating layer, accurately matching the crop growth cycle.

[0006] In a first aspect, the present application provides a slow-release coated fertilizer containing urea, which adopts the following technical solution: A urea-containing slow-release coated fertilizer comprises urea granules and a bio-enzyme polyurethane coating layer coated on the surface of the urea granules, wherein the bio-enzyme polyurethane coating layer has a thickness of 5-50 μm. The bio-enzyme polyurethane coating layer comprises the following raw materials, calculated by weight: 20-25 parts of castor oil, 18-25 parts of castor oil-based polyester polyol, 25-30 parts of hydrophobically modified starch, 16-22 parts of diphenylmethane diisocyanate, 0.03-0.05 parts of a catalyst, 1.5-2 parts of a dispersant, 1.5-2 parts of a high-temperature-resistant bio-enzyme, 2-3 parts of glycerol, and 14-18 parts of N,N-dimethylformamide.

[0007] By adopting the above technical solution, castor oil, as a natural renewable resource, provides hydroxyl (-OH) groups that react with isocyanate (-NCO) to participate in the formation of the polyurethane cross-linked network. This enhances the flexibility and aging resistance of the coating layer and reduces brittleness. Together with castor oil-based polyester polyols, it constructs the polyurethane backbone, increasing the cross-linking density through the polyhydroxy structure. Castor oil-based polyester polyols introduce ester groups through adipic acid, enhancing the rigidity and hydrolysis resistance of the molecular chain. This improves the mechanical strength and degradation controllability of the polyurethane film. It forms a polyol system with castor oil, adjusting the ratio of soft and hard segments in the polyurethane chain and balancing mechanical properties with degradation rate. Hydrophobically modified starch has good hydrophobic properties and significantly reduces the hydrophilicity of starch, significantly reducing water absorption, thereby significantly improving the mechanical properties, waterproofness, and degradation properties of the bio-enzyme polyurethane coating layer. Diphenylmethane diisocyanate (MDI) acts as an isocyanate monomer and reacts with polyols (castor oil and modified polyester polyols) to form polyurethane. Regulating crosslink density directly impacts the mechanical strength and sustained-release rate of the coating. It forms branched crosslinks with glycerol (containing hydroxyl groups), enhancing the stability of the three-dimensional network. The catalyst accelerates the reaction rate of -NCO and -OH groups, precisely controlling the molecular weight distribution of the polyurethane prepolymer and influencing the coating porosity and nutrient release profile. The dispersant promotes uniform dispersion of the hydrophobically modified starch in the polyurethane prepolymer. It prevents filler agglomeration and reduces stress concentration points within the coating. The thermostable enzyme is activated during the late stages of coating degradation (e.g., upon contact with soil microorganisms), accelerating the hydrolysis of the polyurethane segments. It tolerates coating processing temperatures (typically <90°C) and maintains catalytic activity. Together with the microcrystalline structure of the hydrophobically modified starch, it modulates the degradation rate, achieving "slow-release followed by rapid degradation." Glycerol acts as a small molecule chain extender, increasing the flexibility of the polyurethane segments. It regulates the hydrophilic-hydrophobic balance of the coating layer, impacting nutrient diffusion pathways. It reacts with MDI to form urethane bonds, enhancing the toughness of the crosslinked network. N,N-Dimethylformamide (DMF) dissolves MDI and polyols, promoting homogeneous reactions. In summary, this application achieves controlled porosity through the cross-linking density of slow-release castor oil / polyester polyols + MDI cross-linking degree; staged degradation through the reduction of water permeation channels by hydrophobic starch, directional hydrolysis by biodegradable enzymes + disintegration of starch microcrystal structure; rainwater erosion resistance / UV stability by a hydrophobic layer of fluorinated modified starch + ageing-resistant polyurethane segments; and a balance of compressive strength and flexibility through the precise proportioning of these components and the design of the reaction pathway. This coated fertilizer achieves a balance of slow nitrogen release, environmental friendliness, and mechanical durability, meeting the functional requirements of modern agriculture for smart fertilizers.

[0008] Preferably, the method for preparing the hydrophobically modified starch comprises the following steps: S21, according to the weight ratio, 10 parts of corn starch, 2-3 parts of glycerol and 2-3 parts of water were mixed uniformly, and heated to gelatinize to obtain gelatinized starch; S22. Add 10 parts of gelatinized starch to 160 parts of water, add 3-4 parts of sodium citrate, adjust the pH of the solution to 10.5-11, and then add 3-4 parts of vinyl propionate. Heat and stir to react, neutralize, wash, filter, and dry to obtain gelatinized starch propionate. S23. Add 10 parts of gelatinized starch propionate and 3-4 parts of triethylamine to 120 parts of toluene in parts by mass, add dropwise 22-26 parts of a toluene solution of 4,4'-diamino-2,2'-bistrifluoromethylbiphenyl with a mass concentration of 20%, heat and stir to react, add 100-120 parts of anhydrous ethanol to precipitate, filter, wash, and dry to obtain hydrophobically modified starch.

[0009] By adopting the above technical scheme, S21: Preparation of gelatinized starch, glycerol: as a plasticizer, reducing the rigidity of the starch molecular chain, promoting the expansion and gelatinization of starch granules. Heating gelatinization: destroying the crystal structure of corn starch, causing the linear and amylopectin molecules to depolymerize and rearrange, forming a uniform gelatinized starch gel, providing active sites for subsequent modification. S22: Synthesis of gelatinized starch propionate, the ester group of vinyl propionate replaces the hydroxyl group (-OH) in the starch molecule, significantly reducing the hydrophilicity of the starch. S23: Final synthesis of hydrophobically modified starch, triethylamine catalyzes the amidation reaction of the amino group and the ester group to form a stable covalent bond. The introduction of hydrophobic trifluoromethyl (-CF3) groups further enhances the hydrophobicity and chemical stability of the material. The role of the prepared hydrophobically modified starch in the coating layer: 1) Improve mechanical properties and strengthen the molecular structure: the microcrystalline bundle structure of the gelatinized starch is reorganized through hydrogen bonds to form a hard overall skeleton, thereby improving tensile and compressive strength. Cross-linking effect: After reaction with 4,4'-diaminobenzidine derivatives, a three-dimensional cross-linked network is formed, enhancing the mechanical strength and wear resistance of the coating layer. 2) Improved water resistance: Introduction of hydrophobic groups: Propionate groups (-O-CO-C2H5) and trifluoromethyl groups (-CF3) significantly reduce the surface energy of the material, making the coating layer superhydrophobic (contact angle > 110°), reducing water penetration. Water absorption control: After modification, the water absorption rate of the starch decreases by >50%, effectively suppressing the risk of rupture of the coating layer due to moisture absorption and expansion. 3) Regulated degradability and retained enzymatic sensitivity: Although hydrophobic modification reduces the hydrophilicity of starch, biological enzymes (such as α-amylase) can still recognize and degrade the ester bonds and main chain structure, ensuring a degradation rate of ≥90% within 6 months. Controlled degradation rate: The degree of cross-linking and the density of hydrophobic groups can adjust the degradation rate to match the crop's fertilizer requirement cycle. Compatibility with the polyurethane matrix is ​​enhanced, and the ester groups of the hydrophobically modified starch form hydrogen bonds with the carbamate groups (-NH-CO-O-) in the polyurethane, improving interfacial bonding and reducing phase separation. Dispersion uniformity: The dispersant and hydrophobic starch work synergistically to ensure that the coating material is evenly distributed in the polyurethane, forming a dense film layer. Rainwater erosion resistance: The hydrophobic surface reduces rainwater erosion on the coating, with a mass loss rate of ≤3% (GB / T 23348-2021 test), making it suitable for rainy areas. Precise control of sustained release: The hydrophobicity of the coating layer slows the dissolution rate of urea, and combined with film thickness adjustment (5-50μm), a controlled release of 30-120 days is achieved to match the crop growth cycle. In summary, hydrophobically modified starch imparts high strength, hydrophobicity, and controlled degradation properties to the bio-enzyme polyurethane coating layer through molecular structure reorganization (gelatinization), chemical modification (esterification and amidation), and synergistic cross-linking. Its synergistic effect with the polyurethane matrix and other components (such as high-temperature resistant biological enzymes) achieves comprehensive optimization of the fertilizer's slow-release performance, environmental protection and weather resistance, and is the core technical support for the efficiency and greenness of coated fertilizers.

[0010] Preferably, in step S21, the heating and gelatinization temperature is 150-155°C, and the time is 20-30 minutes; in step S22, the heating and stirring reaction temperature is 40-50°C, and the time is 50-60 minutes; in step S23, the heating and stirring reaction temperature is 44-46°C, and the time is 12-14 hours.

[0011] Preferably, the preparation method of the castor oil-based polyester polyol comprises the following steps: S41. Add 45-49 parts by mass of castor oil and 10-12 parts by mass of diethylene glycol to a reactor, mix and stir, add 0.03-0.05 parts of tetrabutyl titanate under nitrogen protection, raise the temperature to 200° C., maintain the temperature for 2-3 hours, and obtain product A; S42. Cool product A to 130° C., add 2.8-3.2 parts of adipic acid under nitrogen protection, slowly raise the temperature to 198° C., maintain the temperature for 4-6 hours, and cool to room temperature after the reaction to obtain product B; S43. Add 0.03-0.05 parts of triethylamine to product B according to parts by mass, and react at room temperature for 40-50 minutes to obtain castor oil-based polyester polyol.

[0012] By adopting the above technical solution, step S41: transesterification reaction between castor oil and diethylene glycol, castor oil (triglyceride) and diethylene glycol (hydrophilic monomer containing two hydroxyl groups) undergo transesterification reaction under the catalysis of tetrabutyl titanate to produce ricinoleyl alcohol (hydroxyl-containing ester compound). More hydroxyl groups (-OH) are introduced to enhance the active sites for subsequent reactions. The molecular weight of castor oil is reduced by transesterification, improving biodegradability. Step S42: polycondensation reaction with adipic acid, the hydroxyl groups in ricinoleyl alcohol undergo polycondensation reaction with adipic acid (dicarboxylic acid) to produce polyester acid chains. Step S43: triethylamine neutralization reaction, the carboxylic acid groups (-COOH) in the polyester acid are neutralized with triethylamine (tertiary amine) to produce polyester polyol ammonium salt. Neutralization of the acidic groups stabilizes the pH value of the product, and the generation of a polyhydroxy structure (polyol), which provides active sites for the subsequent reaction with isocyanate (MDI) to form a polyurethane network. In summary, during the preparation of castor oil-based polyester polyols, castor oil is first reacted with diethylene glycol to form ricinoleyl alcohol, which is then reacted with adipic acid to form castor oil-modified polyester acid. Finally, the castor oil-based polyester polyol is reacted with triethylamine to form the castor oil-based polyester polyol. The resulting castor oil-based polyester polyol exhibits excellent aging resistance and stability, enhancing the mechanical, weatherability, and degradation properties of the bio-enzyme polyurethane coating.

[0013] Preferably, the castor oil comprises the following raw materials: 83 parts of ricinoleic acid, 8 parts of oleic acid, 7 parts of palmitic acid and 2 parts of stearic acid.

[0014] Preferably, the catalyst is dibutyltin dilaurate.

[0015] Preferably, the thermostable biological enzyme is α-amylase.

[0016] Preferably, the dispersant is stearic acid monoglyceride.

[0017] In a second aspect, the present application provides a method for preparing a slow-release coated fertilizer containing urea, which adopts the following technical solution: As a general technical concept, the present application also provides a method for preparing the above-mentioned slow-release coated fertilizer containing urea, comprising the following steps: S91. In a nitrogen atmosphere, castor oil and two-thirds of N,N-dimethylformamide are first added to a reaction vessel in parts by mass and mixed evenly. Then, diphenylmethane diisocyanate, a dispersant, and a hydrophobically modified starch are added and stirred evenly. Then, a catalyst is added and stirring is continued. During the stirring process, the temperature of the reaction system is controlled at 72° C., and the reaction system is observed during the stirring process. The viscosity of the reaction system is adjusted by dropwise addition of the remaining N,N-dimethylformamide to prevent the reaction system from solidifying. After reacting for 3-4 hours, the temperature of the reaction system is lowered to 52° C., and castor oil-based polyester polyol, high-temperature resistant bio-enzyme, and glycerol are added. The reaction is continued for 6-7 hours to obtain bio-enzyme polyurethane. S92, mixing the bio-enzyme polyurethane and ethyl acetate to obtain a bio-enzyme polyurethane liquid; S93. Spray the bio-enzyme polyurethane liquid onto the surface of urea particles preheated to 40-60° C. to form a coating layer, and then solidify the liquid at 70-80° C. for 20-30 minutes to obtain a slow-release coated fertilizer containing urea.

[0018] Preferably, the mass ratio of the bio-enzyme polyurethane to ethyl acetate is 3:2-2.6, and the nitrogen content of the urea granules is ≥46%.

[0019] In summary, this application includes at least one of the following beneficial technical effects: 1. Precise controlled release and efficient nitrogen utilization The release cycle is controllable: By adjusting the thickness of the bio-enzyme polyurethane coating layer (5-50μm), the fertilizer release period can be flexibly controlled (30-120 days) to accurately match the growth cycle requirements of different crops (such as short-cycle vegetables or long-cycle fruit trees).

[0020] High nitrogen retention rate: the total nitrogen content after coating is ≥40%, which reduces nitrogen volatilization and leaching losses through the slow-release mechanism, significantly improves nitrogen utilization rate, and reduces the frequency of fertilization.

[0021] 2. Environmentally friendly and biodegradable Excellent biodegradability: The bio-enzyme polyurethane coating has a degradation rate of ≥90% within 6 months in the natural environment, and the degradation products are non-ecotoxic, avoiding the "white pollution" caused by traditional petroleum-based coating materials.

[0022] Synergistic effect of hydrophobically modified starch: Corn starch is modified through gelatinization, esterification and cross-linking reactions to reduce its hydrophilicity, while enhancing its compatibility with polyurethane, further promoting the degradation of the coating layer.

[0023] 3. Improved mechanical properties and weather resistance Rain erosion resistance: Referring to the GB / T 23348-2021 standard test, after simulating 50mm / h heavy rain for 2 hours, the mass loss rate of the coating layer is ≤3%, which is significantly better than conventional coatings and is suitable for rainy areas.

[0024] Enhanced mechanical strength: Castor oil-based polyester polyols and hydrophobically modified starch work synergistically to improve the tensile strength of the coating layer through hydrogen bonding and microcrystalline bundle structure, making it suitable for mechanical fertilization operations.

[0025] 4.Material stability and function expansion High-temperature resistant enzyme protection: The high-temperature resistant enzyme (such as α-amylase) in the coating layer has an activity retention rate of ≥98% during the processing process, ensuring efficient catalytic decomposition of polyurethane during later degradation.

[0026] Hydrophobic-degradation balance design: By introducing 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl crosslinker, the hydrophilicity of starch is reduced while retaining the enzymatic degradation sites, achieving synergistic optimization of hydrophobic protection and degradation performance. DETAILED DESCRIPTION

[0027] The embodiments of the present application will be described in detail below with reference to the examples, but it will be understood by those skilled in the art that the following examples are merely illustrative of the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, the conditions are carried out according to conventional conditions or manufacturer recommendations. The reagents or instruments used are not specified by the manufacturer and are conventional products that can be purchased commercially.

[0028] In the following examples and preparation examples, 1 part means 100 g.

[0029] Preparation Example 1 Preparation of hydrophobically modified starch The preparation method of hydrophobically modified starch comprises the following steps: S21. Mix 10 parts by mass of corn starch powder (particle size 20 μm, moisture ≤ 14%, ash ≤ 0.15%), 2.5 parts of glycerin, and 3 parts of water, heat to 153° C., and gelatinize for 5 minutes to obtain gelatinized starch. S22. Add 10 parts of gelatinized starch to 160 parts of water, add 3.4 parts of sodium citrate, adjust the pH of the solution to 10.8, then add 3.5 parts of vinyl propionate, heat to 45°C, stir and react for 55 minutes, neutralize, wash, filter, and dry to obtain gelatinized starch propionate; S23. Add 10 parts of gelatinized starch propionate and 3.6 parts of triethylamine to 120 parts of toluene according to their mass fractions, add dropwise 24 parts of a toluene solution of 4,4'-diamino-2,2'-bistrifluoromethylbiphenyl with a mass concentration of 20%, heat to 45°C, stir and react for 13 hours, add 110 parts of anhydrous ethanol to precipitate, filter, wash, and dry to obtain hydrophobically modified starch.

[0030] Preparation Example 2 Preparation of castor oil-based polyester polyol The preparation method of castor oil-based polyester polyol comprises the following steps: S41. Add 47 parts of castor oil and 11 parts of diethylene glycol, by weight, to a reactor, mix and stir, add 0.04 parts of tetrabutyl titanate under nitrogen protection, raise the temperature to 200° C., maintain the temperature and react for 2.3 hours to obtain Product A; wherein the castor oil comprises the following raw materials: 83 parts of ricinoleic acid, 8 parts of oleic acid, 7 parts of palmitic acid, and 2 parts of stearic acid; S42, cooling the product A to 130°C according to the mass fraction, adding 3 parts of adipic acid under nitrogen protection, slowly raising the temperature to 198°C, and maintaining the temperature for 5 hours; after the reaction, cooling to room temperature to obtain product B; S43. Add 0.04 parts of triethylamine to product B according to parts by mass, and react at room temperature for 45 minutes to obtain castor oil-based polyester polyol.

[0031] Example 1 A urea-containing slow-release coated fertilizer comprises urea granules and a bio-enzyme polyurethane coating layer coated on the surface of the urea granules, wherein the bio-enzyme polyurethane coating layer has a thickness of 50 μm, wherein the bio-enzyme polyurethane coating layer comprises the following raw materials, calculated by weight: 20 parts of castor oil, 18 parts of castor oil-based polyester polyol, 25 parts of hydrophobically modified starch, 16 parts of diphenylmethane diisocyanate, 0.03 parts of dibutyltin dilaurate, 1.5 parts of stearic acid monoglyceride, 1.5 parts of α-amylase, 2 parts of glycerol, and 14 parts of N,N-dimethylformamide; The method for preparing the above-mentioned slow-release coated fertilizer containing urea comprises the following steps: S91. In a nitrogen atmosphere, castor oil and two-thirds of N,N-dimethylformamide are first added to a reaction vessel in parts by mass and mixed evenly. Diphenylmethane diisocyanate, stearic acid monoglyceride and hydrophobically modified starch are then added and stirred evenly. Dibutyltin dilaurate is then added and stirred continuously. During the stirring process, the temperature of the reaction system is controlled at 72° C. The reaction system is observed during the stirring process, and the viscosity of the reaction system is adjusted by dropwise addition of the remaining N,N-dimethylformamide to prevent the reaction system from solidifying. After reacting for 3 hours, the temperature of the reaction system is lowered to 52° C., and castor oil-based polyester polyol, α-amylase and glycerol are added. The reaction is continued for 6 hours to obtain bio-enzyme polyurethane. S92, mixing the bio-enzyme polyurethane and ethyl acetate in a mass ratio of 3:2 to obtain a bio-enzyme polyurethane liquid; S93. Spray the bio-enzyme polyurethane liquid onto the surface of urea particles (nitrogen content of 46.3%, particle size of 1.5-3.5 mm) preheated to 40°C to form a coating layer, and then cure the mixture at 80°C for 20 minutes to obtain a slow-release coated fertilizer containing urea.

[0032] Example 2 A urea-containing slow-release coated fertilizer comprises urea granules and a bio-enzyme polyurethane coating layer coated on the surface of the urea granules, wherein the bio-enzyme polyurethane coating layer has a thickness of 50 μm, wherein the bio-enzyme polyurethane coating layer comprises the following raw materials, measured by mass: 25 parts of castor oil, 25 parts of castor oil-based polyester polyol, 30 parts of hydrophobically modified starch, 22 parts of diphenylmethane diisocyanate, 0.05 parts of dibutyltin dilaurate, 2 parts of stearic acid monoglyceride, 2 parts of α-amylase, 3 parts of glycerol, and 18 parts of N,N-dimethylformamide; The method for preparing the above-mentioned slow-release coated fertilizer containing urea comprises the following steps: S91. In a nitrogen atmosphere, castor oil and two-thirds of N,N-dimethylformamide are first added to a reaction vessel in parts by mass and mixed evenly. Diphenylmethane diisocyanate, stearic acid monoglyceride and hydrophobically modified starch are then added and stirred evenly. Dibutyltin dilaurate is then added and stirred continuously. During the stirring process, the temperature of the reaction system is controlled at 72° C. The reaction system is observed during the stirring process, and the viscosity of the reaction system is adjusted by dropwise addition of the remaining N,N-dimethylformamide to prevent the reaction system from solidifying. After reacting for 4 hours, the temperature of the reaction system is lowered to 52° C., and castor oil-based polyester polyol, α-amylase and glycerol are added. The reaction is continued for 7 hours to obtain bio-enzyme polyurethane. S92. Evenly mix the bio-enzyme polyurethane and ethyl acetate in a mass ratio of 3:2.6 to obtain a bio-enzyme polyurethane liquid; S93. Spray the bio-enzyme polyurethane liquid onto the surface of urea particles (nitrogen content of 46.3%, particle size of 1.5-3.5 mm) preheated to 60°C to form a coating layer, and then cure the mixture at 70°C for 30 minutes to obtain a slow-release coated fertilizer containing urea.

[0033] Example 3 A urea-containing slow-release coated fertilizer, comprising urea granules and a bio-enzyme polyurethane coating layer coated on the surface of the urea granules, wherein the bio-enzyme polyurethane coating layer has a thickness of 50 μm, wherein the bio-enzyme polyurethane coating layer comprises the following raw materials, calculated by weight: 22 parts of castor oil, 22 parts of castor oil-based polyester polyol, 27 parts of hydrophobically modified starch, 19 parts of diphenylmethane diisocyanate, 0.04 parts of dibutyltin dilaurate, 1.8 parts of stearic acid monoglyceride, 1.8 parts of α-amylase, 2.3 parts of glycerol, and 16 parts of N,N-dimethylformamide; The method for preparing the above-mentioned slow-release coated fertilizer containing urea comprises the following steps: S91. According to the mass fractions, under a nitrogen atmosphere, castor oil and two-thirds of N,N-dimethylformamide were first added to a reaction vessel and mixed evenly. Then, diphenylmethane diisocyanate, stearic acid monoglyceride and hydrophobically modified starch were added and stirred evenly. Then, dibutyltin dilaurate was added and stirring was continued. During the stirring process, the temperature of the reaction system was controlled at 72°C, and the reaction system was observed during the stirring process. The viscosity of the reaction system was adjusted by dropwise addition of the remaining N,N-dimethylformamide to prevent the reaction system from solidifying. After reacting for 3.4 hours, the temperature of the reaction system was lowered to 52°C, and castor oil-based polyester polyol, α-amylase and glycerol were added. The reaction was continued for 6.7 hours to obtain bio-enzyme polyurethane. S92. Evenly mix the bio-enzyme polyurethane and ethyl acetate in a mass ratio of 3:2.4 to obtain a bio-enzyme polyurethane liquid; S93. Spray the bio-enzyme polyurethane liquid onto the surface of urea particles (nitrogen content of 46.3%, particle size of 1.5-3.5 mm) preheated to 50°C to form a coating layer, and then cure the mixture at 75°C for 25 minutes to obtain a slow-release coated fertilizer containing urea.

[0034] Example 4 The same as Example 3, except that the bio-enzyme polyurethane coating layer has a thickness of 31 μm.

[0035] Example 5 The same as Example 3, except that the bio-enzyme polyurethane coating layer has a thickness of 5 μm.

[0036] Comparative Example 1 The same as Example 3, except that an equal amount of unmodified corn starch is used instead of the hydrophobically modified starch.

[0037] Comparative Example 2 The same as Example 3, except that: an equal amount by mass of modified castor oil polyol AC 009 produced by Ito Corporation of Japan is used to replace the castor oil-based polyester polyol prepared in Preparation Example 2 of this application.

[0038] Comparative Example 3 The same as Example 3, except that: 0 parts of α-amylase.

[0039] Performance testing 1. The enzymatic polyurethane solutions prepared in Examples 1-3 and Comparative Examples 1-3 were placed in molds and cured to obtain corresponding samples. Mechanical properties and water contact angle tests were performed according to GB / T 30693-2014. Water contact angle tests were performed according to ASTM D7334 using a water contact angle tester. Each sample was tested five times, and the average value was calculated. The results are shown in Table 1.

[0040] 2. Degradation Rate Test: The enzymatic polyurethane solutions prepared in Examples 1-3 and Comparative Examples 1-3 were placed in molds and cured to obtain corresponding samples. A soil burial test was performed according to ISO 17556:2019. After 180 days, samples were collected to measure mass loss and calculate degradation rates. The results are shown in Table 1.

[0041] 3. Total nitrogen content test: Slow-release coated fertilizers containing urea were prepared using Examples 1 to 3 and Comparative Examples 1 to 3, respectively, and tested according to the Kjeldahl method (GB / T 2441.1-2001). The results are shown in Table 1.

[0042] 4. Rainwater scour resistance test: The above Examples 1 to 3 and Comparative Examples 1 to 3 were respectively used to prepare slow-release coated fertilizers containing urea. Referring to GB / T 23348-2021, a rainfall intensity of 50 mm / h was simulated for 2 hours, and the mass loss rate was calculated to judge the rainwater scour resistance. The smaller the value, the better the rainwater scour resistance. The results are shown in Table 1.

[0043] 5. Release rate test: The above Examples 1 to 5 and Comparative Examples 1 to 3 were used to prepare slow-release coated fertilizers containing urea. The nutrient slow-release effect was tested according to the international standard ISO 18644 "General requirements for controlled-release fertilizers for fertilizers and soil conditioners" (2016). The urea release rate was as shown in Table 2.

[0044] Table 1 Performance tests 1-4 Table 2 Release rate test project Initial 1-day release rate / % Release rate on the 28th day / % Total release days Example 1 5.35 23.6 112 Example 2 5.17 23.1 116 Example 3 4.95 22.4 120 Example 4 6.12 67.2 73 Example 5 7.83 97.6 33 Comparative Example 1 10.8 45.3 86 Comparative Example 2 9.5 42.3 103 Comparative Example 3 5.05 18.5 195 Analyzing the data in Table 1 and Table 2, we can see that: 1) The urea-containing slow-release coated fertilizers prepared in Examples 1 to 5 have high nitrogen content, controllable release period, environmental friendliness, high degradability, excellent weather resistance, and resistance to rain erosion, and are suitable for agricultural planting, landscaping and other fields.

[0045] 2) A comparative analysis of the performance of the urea-containing slow-release coated fertilizers prepared in Example 3 and Examples 4-5 shows that the release period (30-120 days) can be controlled by adjusting the thickness of the bio-enzyme polyurethane coating layer to accurately match the crop growth cycle.

[0046] 3) A comparative analysis of the performance of the urea-containing slow-release coated fertilizers prepared in Example 3 and Comparative Example 1 demonstrates that the hydrophobically modified starch prepared in this application, through molecular restructuring (gelatinization), chemical modification (esterification and amidation), and synergistic crosslinking, imparts high strength, hydrophobicity, and controlled degradation to the enzyme-enzyme polyurethane coating. Its synergistic effect with the polyurethane matrix and other components (such as the thermostable enzyme) achieves comprehensive optimization of the fertilizer's slow-release performance, environmental friendliness, and weather resistance, providing the core technical support for the efficient and green development of coated fertilizers.

[0047] 4) A comparative analysis of the performance of the urea-containing slow-release coated fertilizers prepared in Example 3 and Comparative Example 2 shows that the castor oil-based polyester polyol prepared in this application, which first reacts castor oil with diethylene glycol to form ricinoleyl alcohol, then reacts with adipic acid to form castor oil-modified polyester acid, and finally reacts with triethylamine to form the castor oil-based polyester polyol, exhibits aging resistance and good stability, and can improve the mechanical properties, weather resistance, and degradation performance of the bio-enzyme polyurethane coating layer.

[0048] 5) A comparative analysis of the performance of the urea-containing slow-release coated fertilizers prepared in Example 3 and Comparative Example 3 shows that the addition of a high-temperature resistant biological enzyme (α-amylase) activates the coating in the later stages of degradation (such as contact with soil microbial environments), accelerates the hydrolysis of the polyurethane chain segments, and can be used to control the release period and accurately match the crop growth cycle.

[0049] The above embodiments are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the above embodiments provide a detailed description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application may still be modified or replaced by equivalents. Any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.

Claims

1. A slow-release coated fertilizer containing urea, characterized in that: The invention comprises urea particles and a bio-enzyme polyurethane coating layer coated on the surface of the urea particles, wherein the bio-enzyme polyurethane coating layer has a thickness of 5-50 μm, wherein the bio-enzyme polyurethane coating layer comprises the following raw materials in parts by mass: 20-25 parts of castor oil, 18-25 parts of castor oil-based polyester polyol, 25-30 parts of hydrophobically modified starch, 16-22 parts of diphenylmethane diisocyanate, 0.03-0.05 parts of a catalyst, 1.5-2 parts of a dispersant, 1.5-2 parts of a high-temperature resistant bio-enzyme, 2-3 parts of glycerol, and 14-18 parts of N,N-dimethylformamide.

2. The slow-release coated fertilizer containing urea according to claim 1, characterized in that: The preparation method of the hydrophobically modified starch comprises the following steps: S21, according to the weight ratio, 10 parts of corn starch, 2-3 parts of glycerol and 2-3 parts of water were mixed uniformly, and heated to gelatinize to obtain gelatinized starch; S22. Add 10 parts of gelatinized starch to 160 parts of water, add 3-4 parts of sodium citrate, adjust the pH of the solution to 10.5-11, and then add 3-4 parts of vinyl propionate. Heat and stir to react, neutralize, wash, filter, and dry to obtain gelatinized starch propionate. S23. Add 10 parts of gelatinized starch propionate and 3-4 parts of triethylamine to 120 parts of toluene in parts by mass, add dropwise 22-26 parts of a toluene solution of 4,4'-diamino-2,2'-bistrifluoromethylbiphenyl with a mass concentration of 20%, heat and stir to react, add 100-120 parts of anhydrous ethanol to precipitate, filter, wash, and dry to obtain hydrophobically modified starch.

3. The slow-release coated fertilizer containing urea according to claim 2, characterized in that: In step S21, the heating and gelatinization temperature is 150-155°C, and the time is 20-30 minutes; in step S22, the heating and stirring reaction temperature is 40-50°C, and the time is 50-60 minutes; in step S23, the heating and stirring reaction temperature is 44-46°C, and the time is 12-14 hours.

4. The slow-release coated fertilizer containing urea according to claim 1, characterized in that: The preparation method of the castor oil-based polyester polyol comprises the following steps: S41. Add 45-49 parts by mass of castor oil and 10-12 parts of diethylene glycol to a reactor, mix and stir, add 0.03-0.05 parts of tetrabutyl titanate under nitrogen protection, raise the temperature to 200° C., maintain the temperature for 2-3 hours, and obtain product A; S42. Cool Product A to 130°C, add 2.8-3.2 parts of adipic acid under nitrogen, and slowly raise the temperature to 198°C. Maintain the temperature for 4-6 hours. After the reaction is complete, cool to room temperature to obtain Product B. S43. Add 0.03-0.05 parts of triethylamine to product B according to parts by mass, and react at room temperature for 40-50 minutes to obtain castor oil-based polyester polyol.

5. The slow-release coated fertilizer containing urea according to claim 4, characterized in that: In step S41, the castor oil includes the following raw materials: 83 parts of ricinoleic acid, 8 parts of oleic acid, 7 parts of palmitic acid and 2 parts of stearic acid.

6. The slow-release coated fertilizer containing urea according to claim 1, characterized in that: The catalyst is dibutyltin dilaurate.

7. The slow-release coated fertilizer containing urea according to claim 1, characterized in that: The high temperature resistant biological enzyme is α-amylase.

8. The urea-containing slow-release coated fertilizer according to claim 1, characterized in that: The dispersant is stearic acid monoglyceride.

9. A method for preparing a urea-containing slow-release coated fertilizer according to any one of claims 1 to 8, characterized in that: The following steps are involved: S91. In a nitrogen atmosphere, castor oil and two-thirds of N,N-dimethylformamide are first added to a reaction vessel in parts by mass and mixed evenly. Then, diphenylmethane diisocyanate, a dispersant, and a hydrophobically modified starch are added and stirred evenly. Then, a catalyst is added and stirring is continued. During the stirring process, the temperature of the reaction system is controlled at 72° C., and the reaction system is observed during the stirring process. The viscosity of the reaction system is adjusted by dropwise addition of the remaining N,N-dimethylformamide to prevent the reaction system from solidifying. After reacting for 3-4 hours, the temperature of the reaction system is lowered to 52° C., and castor oil-based polyester polyol, high-temperature resistant bio-enzyme, and glycerol are added. The reaction is continued for 6-7 hours to obtain bio-enzyme polyurethane. S92, mixing the bio-enzyme polyurethane and ethyl acetate to obtain a bio-enzyme polyurethane liquid; S93. Spray the bio-enzyme polyurethane liquid onto the surface of urea particles preheated to 40-60° C. to form a coating layer, and then solidify the liquid at 70-80° C. for 20-30 minutes to obtain a slow-release coated fertilizer containing urea.

10. The method for preparing a slow-release coated fertilizer containing urea according to claim 9, characterized in that: The mass ratio of the bio-enzyme polyurethane to ethyl acetate is 3:2-2.6, and the nitrogen content of the urea granules is ≥46%.

Citation Information

Cited By

  • Crop fertilizer coating slow-release agent and slow-release coating method

    CN121063989A